1996
DOI: 10.1113/jphysiol.1996.sp021808
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a chimeric mammalian peptide transporter derived from the intestinal and renal isoforms.

Abstract: l. Recently two genes have been identified by expression cloning that encode mammalian epithelial peptide transporters capable of translocating di- and tripeptides and selected peptidomimetics by stereoselective and rheogenic substrate-H+ cotransport. PepT1 from rabbit or human small intestine induces a transport activity with high transport capacity but rather low substrate affinity when expressed in Xenopus oocytes. In contrast, the renal carrier PepT2 is a high affinity-type transporter with a lower maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 16 publications
(12 reference statements)
7
33
0
1
Order By: Relevance
“…To date, some amino acid residues or domains in PEPT1 have been revealed functionally important, and the results in the present study are largely compatible with those earlier findings: 1) Previous studies on PEPT1 and PEPT2 chimeras (Doring et al, 1996) suggested that the large extracellular loop between TM9 and TM10 is not essential for phenotypical characteristics of transporter function. This observation is in good agreement with our results: five cSNPs located on this loop have little influence on transporter function in terms of pH dependence, substrate uptake kinetics, and inhibition specificity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To date, some amino acid residues or domains in PEPT1 have been revealed functionally important, and the results in the present study are largely compatible with those earlier findings: 1) Previous studies on PEPT1 and PEPT2 chimeras (Doring et al, 1996) suggested that the large extracellular loop between TM9 and TM10 is not essential for phenotypical characteristics of transporter function. This observation is in good agreement with our results: five cSNPs located on this loop have little influence on transporter function in terms of pH dependence, substrate uptake kinetics, and inhibition specificity.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to identification of those functionally important residues in PEPT1, it has been proposed that the N-terminal one-half including TM7, TM8, and TM9 is the region of PEPT1 responsible for proton and substrate recognition (Doring et al, 1996;Fei et al, 1998;Terada et al, 2000), and a recent study with cysteine mutagenesis on PEPT1 revealed that TM5 may be part of the substrate translocation pathway (Kulkarni et al, 2003). Additionally, it has been speculated that the C-terminal region, although not directly involved in substrate recognition and binding, may be important for either protein trafficking or functional regulation (Doring et al, 1996). Located on the membrane boundary of TM10 in C-terminal portion of PEPT1, Pro 586 was shown not to be important for protein function in terms of pH-dependent uptake, Gly-Sar affinity, and inhibitor specificity, because P586L behaved similarly to the reference gene with respect to these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This region is poorly conserved among vertebrate PEPT1 orthologs. Moreover, this region is not involved in the transport activity, as assessed by computational, site-directed mutagenesis, chimeric, and other approaches (36)(37)(38)(39)(40)(41)(42)(43). Insertion of the VDMSRKS domain into this region does contribute to the cold adaptation of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Doring et al (1997) performed a functional analysis of peptide transport by using a chimeric transporter obtained from the intestinal and renal isoforms.…”
Section: 1)mentioning
confidence: 99%